Proton Therapy for Skull Base Chondrosarcoma - Tang, Dennis M.; Cutri, Raffaello M.; Wu, Arthur W.; Patil, Chirag; Zumsteg, Zachary S. (Journal of Neurological Surgery Reports, 2023)
Chondrosarcoma is a type of an endochondral bone malignancy that is primarily treated surgically with radiation therapy used in the adjuvant setting or in cases of unresectable disease. Proton therapy has potential advantages compared with traditional photon therapy for the treatment of tumors in close proximity to critical structures due to the theoretic lower exit dose. Studies have shown improved survival in patients with skull base chondrosarcoma who undergo proton therapy. However, there is a lack of randomized data. Further studies are needed to define the role of proton therapy in the treatment of skull base chondrosarcoma.
Keywords: skull base; chondrosarcoma; radiation therapy; proton therapy